The Small Monetary Incentive for Blood Pressure Self-monitoring Behavior in Online Hypertension Management - Tang, Wensheng; Pang, Peng; Zhang, Han; Zhang, Yong (British Journal of Healthcare and Medical Research, 2025)
Objective: To assess the effectiveness of two methods of delivering a fixed total monetary incentive to improve blood pressure self-monitoring behavior in hypertensive patients. Design: This study is a randomized, double-blinded controlled trial. Methods: A 3-arm trial with 99 participants, randomly assigned to a control group and two intervention groups (1:1:1 ratio). Participants utilized internet-based blood pressure monitors and implemented guideline-based standardized hypertension management through an online platform. The two intervention groups received different time-dependent incentives (1 RMB per day) over a 3-month period: immediate or delayed. Results: In the first month, no significant difference was observed in blood pressure self-monitoring among three groups (P > 0.05). In the second month, the intervention groups showed significantly higher monitoring days compared to the control (immediate incentive: 21.5 days vs. 16.3 days, P = 0.009; delayed incentive: 21.3 vs. 16.3 days, P = 0.029). In the third month, the intervention groups had significantly more measurements (31.1 and 31.4 vs. 17.9 times, P = 0.013 and P = 0.014). Monitoring behavior declined in all groups over 6 months, with the delayed incentive group declining at a slower rate (p < 0.001 for regression coefficient comparison). Conclusions: Monetary incentives effectively improved blood pressure monitoring behavior in the short term. However, their impact diminished after the incentives were withdrawn, with delayed incentives resulting in a slower decline. Small, delayed monetary incentives may provide benefits for remote hypertension management. Future research should investigate the long-term effects and clinical outcomes.